Mengapa Masyarakat Kecamatan Entikong Kabupaten Sanggau Berobat ke Sarawak, Malaysia - Feny Widiyastuty; Chriswardani Suryawati; Septo Pawelas Arso (Jurnal Kesehatan Komunitas, 2023)
An increasing number of Indonesians are seeking medical treatment abroad, causing the government to lose potential revenue streams from the health services industry. People in border regions have a wonderful opportunity to use health treatment facilities in neighboring countries because of their close proximity to them. One such community is in the Entikong District, which is next to Sarawak, Malaysia. The purpose of this study is to examine the factors that influence Entikong District residents' use of Sarawak health services. This study is an observational quantitative study with a cross-sectional design. The research population consists of 9,337 residents of the Entikong District aged 20 to 50. A proportional random sampling method was used to pick 100 respondents for the research sample. This research was conducted from September to October 2022. The data were analyzed using the chi-square test and logistic regression. The findings showed that income (p=0.012), reference group (p=0.026), and perceptions of health services (p=0.009) were associated with the use of health services by the residents of Entikong District in Malaysia, however education (p=0.961) and occupation (p=0.589) were not. There is a relationship between income, reference groups and perceptions of health services with utilization of health services. There is no relationship between education and work with service utilization. People with high incomes have more potential to take advantage of Sarawak health services. It is hoped that the Entikong Community Health Center, the Sanggau District Health Office, and the Sanggau District Government will be able to provide quality primary healthcare facilities and referral healthcare facilities in border areas to increase competitiveness with Sarawak health service facilities.